Communication Approches in Enhancing The Effectiveness of Community Fund Collection in The RW 006, Kelurahan Cipinang Cempedak, East Jakarta - Dema, Yosef; Mutiarawati, Elisabeth Vita; Billy, Yohanes L. (Jurnal Komunikasi dan Bisnis, 2024)
This study investigates the effectiveness of communication strategies in enhancing community fund collection in RW 006, Kelurahan Cipinang Cempedak, East Jakarta, through the lens of Social Capital Theory and Communication Theory. By addressing socio-economic disparities and digital literacy issues, the research aims to provide actionable insights for local authorities. A mixed-method approach, combining qualitative interviews with Neighborhood Association leaders and residents, as well as observations of community meetings, was employed. The analysis reveals that a hybrid communication strategy, integrating traditional meetings and digital platforms like WhatsApp, significantly enhances community engagement and fund collection. However, digital literacy and socio-economic disparities present significant barriers. Transparent reporting and regular updates are essential for building trust and encouraging participation. The findings underscore the importance of inclusive communication strategies that address both digital literacy and socio-economic challenges, thereby fostering community participation and optimizing fund collection efforts in urban neighborhoods.